Psaironeura angeloi, a new species of damselfly (Zygoptera: Coenagrionidae) from Central and South America - Tennessen, Kenneth J. (Zootaxa, 2016)
Psaironeura angeloi sp. nov. (Holotype male deposited in FSCA: ECUADOR, Esmeraldas Province, small stream 5.6 km NW of Lita, 00.893°N 78.510°W, 4.II.1997, KJT leg.) is described and illustrated based on specimens from Ecuador, Panama, Costa Rica, and Nicaragua, bringing the total number of species in the genus to five. The new species is closely related to P. remissa (Calvert), a Mexican/northern Central American species with broad, foliate male cerci, but is distinct in that the long flagella of the genital ligula lack a small sharp spine unique to P. remissa, labrum and clypeus are orange-red, and the back of the head is mostly pale in both males and females. In life, the eyes of the new species are bright red in males versus green and black in P. remissa.